2011
DOI: 10.1007/s11248-011-9547-1
|View full text |Cite
|
Sign up to set email alerts
|

A 3,387 bp 5′-flanking sequence of the goat alpha-S1-casein gene provides correct tissue-specific expression of human granulocyte colony-stimulating factor (hG-CSF) in the mammary gland of transgenic mice

Abstract: A new expression vector containing the 1,944 bp 5'-flanking regulatory region together with exon 1 and intron 1 of the goat alpha-S1-casein gene (CSN1S1), the full-sized human granulocyte colony-stimulating factor gene (hGCSF) and the 3'-flanking sequence of the bovine CSN1S1, was created. The vector DNA was used for generation of four mouse transgenic lines. The transgene was integrated into chromosomes 8 and 12 of two founders as 2 and 5 copies, respectively. Tissue-specific secretion of hG-CSF into the milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…We used a qPCR technique to estimate the copy number of the transgene in each line of the transgenic mice16. The results indicated that the transgene copy numbers in the founders were different, ranging from 7 to 20.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a qPCR technique to estimate the copy number of the transgene in each line of the transgenic mice16. The results indicated that the transgene copy numbers in the founders were different, ranging from 7 to 20.…”
Section: Resultsmentioning
confidence: 99%
“…The transgene copy number in the transgenic mice was determined by qPCR as described previously16 with primers designed for a single copy control gene (lymphotoxin B gene: Ltb) and the pBC1-INS transgene. The primer sequences for Ltb have been described previously16, and the primer sequences for the pBC1-INS were pBC1-INS-F and pBC1-INS-R (Table 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic activity of a foreign protein can be generated by unexpected events such as ectopic transgene expression or via a non-exocrine pathway of the protein from the target tissue to the blood (Rülicke and Hübscher, 2000;Dunn et al, 2005). In this context, investigation of ectopic gene expression in different tissues/organs is an important and unavoidable step to the phenotypic characterization of transgenic animals (Huang et al, 2012;Serova et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, thermal asymmetric interlaced PCR (TAIL-PCR), based on nest PCR and randomly primed PCR category (Liu and Chen, 2007), has become an extremely valuable and versatile tool for detecting insertion sites of foreign genes. TAIL-PCR methods have been successfully used to clone unknown sequences adjacent to known vector sequences in mice (Pillai et al, 2008, Serova et al, 2012 and pig (Zhou et al, 2013); however, there are few reports focusing on transgenic goats because the goat genome has not been completely sequenced.…”
Section: Introductionmentioning
confidence: 99%